65.1k views
0 votes
(5-9i)-(2-6i)+(3-4i)

1 Answer

3 votes

================================

Simplifying - Solution and Explanation

================================

Hello! So...

We are given the following:


(5-9i)-(2-6i)+(3-4i)

_____________________________________________

1. Simplify the given expression.


(5-9i)-(2-6i)+(3-4i)=5-9i-(2-6i)+3-4i

_____________________________________________

2. Group the like terms.


-9i-4i(-2-6i)+5+3

_____________________________________________

3. Add similar elements (
-9i-4i=-13i ).


=-13i-(2-6i)+5+3

_____________________________________________

4. Add the numbers (
5+3=8 ).


-13i-(2-6i)+8

_____________________________________________

5. Remove the parentheses (
-(a+bi)=-a-bi ).


-13i+-2-(-6)i+8

_____________________________________________

6. Group the like terms.


-13i-(-6)i-2+8

_____________________________________________

7. Add similar elements (
-13i-(-6)i=-7i ).


-7i-2+8

_____________________________________________

8. Add the numbers (
-2+8=6 ).


-7i+6

_____________________________________________

9. Rewrite in standard complex form.


6-7i

^Hence, our solution.

_______________________________________________________

Hope this helps! If so, lmk! If you need anything else, feel free to comment below and I'll see what else I can do to assist you further. But for now, thank you for your time and good luck!

User CC Inc
by
5.6k points